2016
DOI: 10.1159/000448905
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric Copy Number Variations: The Importance of 4p/4q Deletions in Patients with Congenital Anomalies and Developmental Disability

Abstract: The most prevalent structural variations in the human genome are copy number variations (CNVs), which appear predominantly in the subtelomeric regions. Variable sizes of 4p/4q CNVs have been associated with several different psychiatric findings and developmental disability (DD). We analyzed 105 patients with congenital anomalies (CA) and developmental and/or intellectual disabilities (DD/ID) using MLPA subtelomeric specific kits (P036 /P070) and 4 of them using microarrays. We found abnormal subtelomeric CNVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
3
0
1
Order By: Relevance
“…The majority of the examined patients with an 8p23 deletion were characterized using traditional techniques, including G-banded karyotyping, fluorescence in situ hybridization (FISH), microsatellite marker genotyping and multiplex ligation-dependent probe amplification (MLPA), with limited resolution and low efficiency. Therefore, an accurate definition of the locations, sizes and genes contained in the deletions has been difficult to obtain ( 5 , 9 , 20 23 ). Nevertheless, few microarray-based molecular studies have been performed to investigate these deletions.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the examined patients with an 8p23 deletion were characterized using traditional techniques, including G-banded karyotyping, fluorescence in situ hybridization (FISH), microsatellite marker genotyping and multiplex ligation-dependent probe amplification (MLPA), with limited resolution and low efficiency. Therefore, an accurate definition of the locations, sizes and genes contained in the deletions has been difficult to obtain ( 5 , 9 , 20 23 ). Nevertheless, few microarray-based molecular studies have been performed to investigate these deletions.…”
Section: Introductionmentioning
confidence: 99%
“…Anomalies have been reported affecting the brain (ventriculomegaly, cortical atrophy and prominent ventricles, large occipital encephalocele) [12][13][14], eyes (bilateral hypermetropia, pigmentary retinal degeneration, microphthalmia) [15][16][17][18], cleft palate and Pierre Robin syndrome [3,5,7,[19][20][21], heart (enlarged right atrium and ventricle, small atrial septal defect, abnormal structure and function of both ventricles and double inferior vena cava, coarctation of the aorta and interventricular communication, both valvar pulmonic stenosis, cor triatriatum) [3,8,[22][23][24], kidneys (duplicated left intrarenal collecting system, polycystic kidney, bilateral extrarenal pelvis dysplastic cystic kidneys) [3, 9, 24-26], genital defects [27], limb development disorder (irregularity of the outline of the distal phalanx of the 4th digit, rudimentary left thumb with absence of right thumb, bilateral absence of ulna) [28][29][30][31]. Craniofacial dysmorphism has frequently been reported with signs that are not speci cally diagnostic [32][33][34][35][36], as well cognitive involvement [17,[37][38][39][40][41], de cit of growth [25,34] and epileptic seizures [22,25]. Other reported anomalies include congenital hearing impairment [18, 42], hypercalciuria and kidney calci cation [43], familial combined hyperlipidemia <...…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the prevalence of independent deletions at 4p/4q involves PIGG, TRIML2, and FRG1. This suggests a possible implication of FRG1 in neurodevelopmental disorders (Novo-Filho et al, 2016). This gene is also susceptible of false positive results (http:// massgenomics.org/2013/06/ngs-false-positives.html).…”
Section: De Novo Variant Analysismentioning
confidence: 99%